2019
DOI: 10.12944/crnfsj.7.3.27
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of the Polyphenolic Content and Antioxidant Properties of Rubus Glaucus Benth

Abstract: The Andes berry (Rubus glaucus Benth) has an ongoing production in Colombia and is considered a competitive market product with the potential for exportation and broad applications in agroindustry because of its high content of antioxidants, nutrients, and proteins, which are keys to a balanced diet. In this study, the effect of an Aloe vera gel coating on the preservation of the nutraceutical properties of the Andes berry was evaluated by measuring the antioxidant capacity and the total phenolic content of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
(30 reference statements)
3
3
0
Order By: Relevance
“…By having low water solubility and a higher permeability, it will be less likely that the coating will be susceptible to deterioration during fruit storage. The results obtained in this study demonstrated the ability of the Aloe vera coating to extend the shelf life of Andean blackberry fruit, similar results were obtained by [23] who evaluated the preservation of the polyphenolic content and antioxidant properties of Rubus glaucus Benth.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…By having low water solubility and a higher permeability, it will be less likely that the coating will be susceptible to deterioration during fruit storage. The results obtained in this study demonstrated the ability of the Aloe vera coating to extend the shelf life of Andean blackberry fruit, similar results were obtained by [23] who evaluated the preservation of the polyphenolic content and antioxidant properties of Rubus glaucus Benth.…”
Section: Discussionsupporting
confidence: 88%
“…According to the study carried out by Velasquez-Castro, et al, (2019) [23], the total phenols content did not show differences between coated and uncoated fruits (p > 0.05), while during storage the differences became statistically significant, a similar behavior found in this study. On the first day, the total phenol content was 316.94 ± 2.75 mg GAE L −1 sample and 329.44 ± 6.285 mg GAE L −1 sample and increased significantly to 450 ± 3.93 mg GAE L −1 sample and 470 ± 3.93 mg GAE L −1 sample after storage 19 days for the coated and uncoated fruits, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations